Embeddedness and collaborative venture networks among Korean construction firms for overseas construction projects - Son, JeongWook; Han, Seung Heon; Rojas, Eddy M. (Journal of Civil Engineering and Management, 2015)
Finding competent collaborators while executing construction projects overseas is of paramount importance for project success. The partner choice and project performance cannot be understood only from an economic viewpoint because it is constrained by the firms’ embeddedness in social relations. Based on this premise, this paper provides not only a theoretical explanation of the impact of structural and relational embeddedness on firms’ economic behaviour and outcomes, but also empirical evidence by analysing the collaborative process among Korean construction firms working overseas during the past 18 years. Three conclusions are drawn. First, the inter-firm network, at least asymptotically, has scale-free network properties with variance. Second, the network retained endogamic characteristics in that a great majority of smaller firms had worked with only one large firm, forming strong subgroups. Last, there is a plausible evidence of the impact of both structural embeddedness and relational embeddedness on profits.